Western diet-induced ultrastructural changes in mouse pancreatic acinar cells - Lipovšek, Saška; Dolenšek, Jurij; Dariš, Barbara; Valladolid-Acebes, Ismael; Vajs, Tanja; Leitinger, Gerd; Stožer, Andraž; Skelin Klemen, Maša (Frontiers in Cell and Developmental Biology, 2024)
Mouse models of diet-induced type 2 diabetes mellitus provide powerful tools for studying the structural and physiological changes that are related to the disease progression. In this study, diabetic-like glucose dysregulation was induced in mice by feeding them a western diet, and light and transmission electron microscopy were used to study the ultrastructural changes in the pancreatic acinar cells. Acinar necrosis and vacuolization of the cytoplasm were the most prominent features. Furthermore, we observed intracellular and extracellular accumulation of lipid compounds in the form of lipid droplets, structural enlargement of the cisternae of the rough endoplasmic reticulum (RER), and altered mitochondrial morphology, with mitochondria lacking the typical organization of the inner membrane. Last, autophagic structures, i.e., autophagosomes, autolysosomes, and residual bodies, were abundant within the acinar cells of western diet-fed mice, and the autolysosomes contained lipids and material of varying electron density. While diets inducing obesity and type 2 diabetes are clearly associated with structural changes and dysfunction of the endocrine pancreas, we here demonstrate the strong effect of dietary intervention on the structure of acinar cells in the exocrine part of the organ before detectable increases changes in plasma amylase activity, which may help us better understand the development of non-alcoholic fatty pancreas disease and its association with endo-and exocrine dysfunction.